Isolamento químico e avaliação de bioatividade de frações do fruto de noni (Morinda citrifolia L.) - Guidoti, David Teixeira (2015)
Morinda citrifolia (Rubiaceae), popularly known as noni, is distributed in the tropical regions of Central and Southern Africa and throughout the Caribbean islands, Australia, China, Malaysia, Indonesia, India and North and South America. The plant has been used for more than two thousand years as folk medicine due to its therapeutic and nutritional qualities. The plant has several bioactive compounds, such as scopoletin, a phenolic compound derived from coumarin, which controls serotonin levels in the organism, with anti-inflammatory, antioxidant, anti-proliferation and pro-apoptotic activities. The objective of this current assay was to identify fractions of the noni fruit as potential chemoprevention sources by isolating bioactive compounds and by bio-guide study of cytogenotoxicity, mutagenicity and antimutagenicity performed in the culture of human normal and tumor cells and in the filamentous fungus Aspergillus nidulans. Concentrations varied between 0 and 500 μg mL-1 diluted in dimethyl sulfoxide. The isolation of a compound was performed from the fraction ethyl acetate by thin layer chromatography, identified as isoscopoletin by nuclear magnetic resonance. Crude ethanol extract and ethyl acetate and n-hexane fractions revealed an anti-proliferation effect against human cell-tumor strains, which may be safely employed at low concentrations. The ethyl acetate fraction was not cytogenotoxic for HepG2 cells nor cytotoxic for A. nidulans, but had an antimutagenic effect in all concentrations and it was also pro-apoptotic at concentrations 25 and 250 μg mL-1 at the times and types of treatment employed. On the other hand, n-hexane fraction triggered the proliferation of HepG2 cells after a 48h exposure and had a genotoxic effect at higher concentrations. Results are relevant for the elucidation of the cytotoxic and genotoxic effects of the fractions and in the preliminary identification of complex extracts as a protecting activity of genetic material as a supplement in the preparation of phytotherapeutic and prophylactic drugs and in future studies to identify chemoprevention compounds.